Genetic consultations in cases of unexplained fractures and haemorrhage: an evidence-based approach. Issue 1 (16th February 2021) - Shur, Natasha; Summerlin, Maxwell L.; Robin, Nathaniel H.; Moreno-Mendelson, Adam; Shalaby-Rana, Eglal; Hinds, Tanya
Abstract : Purpose of review: When infants and young children present with suspected physical abuse, it is critical to follow standard guidelines and rule out alternative causes of fracture and haemorrhage. A multidisciplinary team involved in the initial evaluation typically includes paediatrics, radiology, child protective services and/or law enforcement, and in complex cases, haematology, neurology, and genetics. A comprehensive genetics consultation includes review of the history of present illness, birth and past medical history, review of growth curves, family history, physical examination, radiological findings, and when indicated, biochemical and/ or genetic testing. Recent findings: A number of reports have mischaracterized several genetic disorders as child abuse mimics. There is a difference between a differential diagnosis, which includes every condition that can cause a fracture and/or subdural haemorrhage, and a mimic, so called because it can be difficult to differentiate from child abuse. In this review, we discuss the differential diagnosis for infantile fractures and subdural bleeds, highlight cardinal signs and symptoms of genetic disorders, and demonstrate that these genetic disorders can be readily differentiated and diagnosed using a stepwise approach. Genetic disorders rarely, if ever, are truly mimics of child physical abuse. Summary: In cases of suspected child physical abuse, multidisciplinary evaluations by paediatric specialists, keen clinical judgment, complete physical examinations, and judicious testing provides an evidence-based, time tested approach to excluding genetic disorders and diagnosing suspected child physical abuse.